Rekomendasi Posting Promosi pada Sosial Media Berdasarkan Pengelompokan Hasil Penjualan Produk (Studi Kasus: Maula Hijab) - Taufaldisatya Wijatama Diwangkara; Ulfi Saidata Aesyi; Netania Indi Kusumaningtyas (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Maula Hijab is an MSME (Small and Micro Medium Enterprises) located in Sidomoyo, Godean District, Sleman Regency, Yogyakarta Special Region Province that sells Muslim clothing products. Maula Hijab sells its products directly and through marketplace platforms such as Shopee, Lazada, and Tokopedia. In addition, Maula Hijab promotes its products through social media, one of which is Instagram. Social media is used to promote Maula Hijab products, but there is a decrease in the number of viewers reached by the Maula Hijab Instagram account. In addition, a decline in sales of Maula Hijab was found. Therefore, it is necessary to analyze the level of product promotion performance on Instagram on product sales. To analyze the two data, the Data Mining technique used in this study is K-Means Clustering. The K-Means Clustering algorithm is used to group, classify, or group a set of objects based on their attributes or features into a number of similar groups called clusters. This study aims to provide recommendations for promotion of Maula Hijab products using the K-Means Clustering algorithm. This study uses the K-Means Clustering method. The final result of this research is that 3 product clusters are produced, namely product clusters that are recommended to be promoted more often, product clusters that can be re-promoted, and product clusters that have good promotions. The recommendation system built can run to retrieve Instagram data and process the data to produce output in the form of product promotion recommendations.